Protected natural areas and environmental territorial planning in the Argentina-Paraguay cross-border area (Huellas, 2025)
This article assesses the environmental regimes adopted by Argentina and Paraguay in the transboundary space they share in the Gran Chaco, focusing on the definition and implementation of natural protected areas and environmental territorial planning instruments, with special attention to native forests. To this end, the study focuses on the province of Formosa (Argentina) and the departments of Boquerón and Presidente Hayes (Paraguay), where the advance of the agricultural frontier is exerting an increasing pressure on natural goods. Evidence is presented from research based on the analysis of official documents (legislation and technical reports) and specialized academic literature, and on the systematization of information through the use of data matrices and Geographic Information Systems. The evidence gathered highlights the moderate scope of environmental policies, which configure scenarios tolerant to the territorial expansion of the agribusiness production model, and the growing disconnection between the legal frameworks, conservation strategies and forms of territorial management implemented by both countries. Within this framework, the need to rethink environmental management from a perspective that considers its transboundary approach is highlighted.
Keywords: Environmental regimes; borders; natural protected areas; environmental territorial planning; Gran Chaco